Global social sustainability and inclusion: The "voice" of social and environmental imbalances - Andriy Krysovatyy; Iryna Zvarych; Oksana Brodovska; Roman Zvarych (Journal of Risk and Financial Management, 2022)
Background: Global environmental and social research strengthens the protection of people and the environment, develops national capacity for social and environmental management and enables significant progress in terms of transparency, accountability, nondiscrimination and public participation. The support of the general public plays a key role, as it contributes to making public institutions more transparent, accountable and efficient and promotes ground-breaking solutions to complex development challenges. Citizen engagement seems particularly vital throughout the crises such as the COVID-19 pandemic, as the efficiency of response efforts may frequently depend upon micro-level behavioral changes. The objective of this paper is to provide a complex evaluation and rating of countries based on the social component of the global inclusive circular economy, taking into account the shocks and reverberations experienced by the economy as a whole caused by the COVID-19 and war in Ukraine. The results are presented as a global ranking of countries based on the social component of the global inclusive circular economy. They confirm the high value of this component in the integrated indicator, which validates the hypothesis that inclusiveness is a necessary aspect of the global circular economy. The research results identify the countries capable of offering the best management solutions to social disbalances and other weaknesses, as well as the countries in need of model examples to tackle these issues.
Keywords: 650; poverty; global inclusive circular economy; global sustainability; social inclusion